The Economic Function of a Stock Exchange - Schwartz, Robert A.; Byrne, John Aidan; Wheatley, Lauren (Zicklin School of Business Financial Markets Series, 2015)
In recent years, exchanges on both sides of the Atlantic have been extensively reengineered, and their organizational structures have changed from non-profit, membership organizations to for-profit, demutualized organizations. Concurrently, new alternative trading systems have emerged and the traditional functions of broker/dealer firms have evolved. How have these changes affected the delivery of that mission? How has the efficiency of capital raising in the IPO market been impacted? These are among the key questions addressed in this book, titled after the Baruch College Conference, The Economic Function of a Stock Market. Featuring contributions from a panel of scholars, academicians, policymakers, and industry leaders, this volume examines current issues affecting market quality, including challenges in the marketplace, growth opportunities, and IPO capital raising in the global economy. The Zicklin School of Business Financial Markets Series presents the insights emerging from a sequence of conferences hosted by the Zicklin School at Baruch College for industry professionals, regulators, and scholars. Much more than historical documents, the transcripts from the conferences are edited for clarity, perspective and context; material and comments from subsequent interviews with the panelists and speakers are integrated for a complete thematic presentation. Each book is focused on a well delineated topic, but all deliver broader insights into the quality and efficiency of the U.S. equity markets and the dynamic forces changing them.